Husbands’ and Wives’ Alcohol Use Disorders and Marital Interactions as Longitudinal Predictors of Marital Adjustment - Cranford, James A. (2011)
This longitudinal study tested the hypothesis that marital interactions mediate the associations between wives’ and husbands’ lifetime alcoholism status and their subsequent marital adjustment. Participants were 105 couples from the Michigan Longitudinal Study (MLS), an ongoing multimethod investigation of substance use in a community-based sample of alcoholics, nonalcoholics, and their families. At baseline (T1), husbands and wives completed a series of diagnostic measures and lifetime DSM-IV diagnosis of alcohol use disorder (AUD) was assessed. Couples completed a problem-solving marital interaction task 3 years later at T2, which was coded for the ratio of positive to negative behaviors (P/N) was calculated. Couples also completed the Dyadic Adjustment Scale (DAS; Spanier, 1976) at T4 (9 years after T1 and 6 years after T2). Moderate to strong positive correlations were observed between husbands’ and wives’ lifetime AUD, P/N ratio, and dyadic adjustment. Based on an Actor-Partner Independence Model (APIM) framework, results from structural equation modeling showed that husbands’ lifetime AUD was negatively associated with wives’ P/N ratio at the 3 year point, but was not related to their own or their wives’ marital adjustment 9 years from baseline. However, wives’ lifetime AUD had direct negative associations with their own and their husband’s marital satisfaction 9 years later, and wives’ P/N ratio was positively related to their own and their husband’s marital satisfaction 6 years later. Results indicate that marital adjustment in alcoholic couples may be driven more by the wives’ than the husbands’ AUD and marital behavior.